DETERMINATION OF THE PHYSICAL AND MECHANICAL PROPERTIES OF 1:4 MORTAR WITH ADDITION OF RICE HUSK AS A PARTIAL REPLACEMENT OF FINE AGGREGATE - Haidee Yulady Jaramillo; Author; July Andrea Gomez Camperos (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Agricultural residues can be used as a resource for construction materials, one of these residues is rice husk which is generated in large quantities during rice processing. The aim of this article is to determine the physical and mechanical properties of a 1:4 dosage mortar with the addition of rice husks as a partial replacement of fine aggregate, seeking the possibility of innovating with the creation of a composite material with low environmental impact and optimal physical and mechanical performance characteristics. This research was carried out in five stages: Stage I, obtaining the materials for the mortar. Stage II, mix design. Stage III, tests to obtain the physical-mechanical properties of the mortar with a dosage of 1:4 with and without the addition of rice husks. Stage IV, selection of the specimens of the mortar for plastering with the addition of rice husks with the dosage that presented the best results in the physical-mechanical properties and the specimens without the addition of fibres. The selected materials were sand, cement type I "General use", water and rice husk as a reinforcing agent. The mix design allowed the production of mortar cubes and beams in 4 groups: 0%, 1%, 3% and 5% of rice husk, with respect to the sand content. The mortar with rice husks showed an increase in flexural strength compared to the mortar without rice husks between 5 and 19%. The inclusion of rice husks as a partial replacement of the fine aggregate in the 1:4 mortar is adequate and meets the requirements for this material.